Tabayyun sebagai Prinsip Etik Jurnalistik Islam: Studi Hukum Islam atas Pemberitaan Pesantren tanpa Riset - M. Havy Sa’dullah; Achmad Lubabul Chadziq (MASADIR: Jurnal Hukum Islam, 2025)
Abstract: This study aims to examine the principle of tabayyun as the ethical foundation of Islamic journalism in responding to the phenomenon of pesantren (Islamic boarding school) reporting conducted without adequate research. Such cases reflect an ethical and epistemic crisis in modern journalism, which often prioritizes speed and sensationalism over verification and accuracy. Using a normative and literature-based approach, this research explores the foundations of Islamic law, the ethical values of communication, and relevant theories of contemporary journalism. The findings indicate that tabayyun, as emphasized in the Qur’anic verse Al-Hujurat [49]:6, represents not only a moral obligation but also an epistemological framework that demands responsibility in the production and dissemination of information. This principle aligns with the values of verification and truth-seeking found in modern media ethics, yet expands them by incorporating spiritual and social dimensions. Integrating tabayyun into journalistic ethics can strengthen informational justice, preserve the dignity of religious institutions, and restore journalism’s mission toward public welfare. Therefore, this study highlights the importance of revitalizing Islamic law as a relevant ethical guideline within today’s media ecosystem.